A new method of text information hiding based on open channel. (3rd September 2019) - Ren, Yongjun; Ma, Wenyue; Wang, Xiaohua
Text is one of most constantly and widely used information carriers. Comparing with several other carriers, a new method of text information hiding based on open channel has been put forward in the article. The public normal text has been used to transmit information directly without any changes in order to hide it. At the same time, this hidden information negotiates with the intended recipient to produce the session key. The text including the location of hidden information and including the associated hidden rules delivers information through the session key. Besides, this method avoids stenographic testing used by attackers unless they break the session key, which ensures the hidden information's safety. The instruction protocol of hidden information serves as basic tool in proposed method. In the paper, the idea of the implicit authentication in the MTI protocol families (key agreement protocol constructed by Matsumoto, Takashima and Imai) derives from an identity-based protocol without pairing. Moreover, this proposed protocol is provably-secured in CK model (Canettikrawczyk model) for text information hiding.